Understanding sense of belonging of fraternity and sorority members with disabilities: a phenomenological study - Varland, Charlie, author; Ellis, Michael, advisor; Kuk, Linda, committee member; Lange, Alex, committee member; Sample, Pat, committee member (Colorado State University. Libraries, 2025)
Research suggests that college students with disabilities benefit from and have a greater sense of belonging because of involvement in student organizations. However, a gap exists within the literature specifically in studies focused on how students with disabilities develop a sense of belonging through their involvement as members of a fraternity or sorority. Using the Social Justice Model of Disability as a theoretical lens, this phenomenological study focuses on the experiences that impact sense of belonging of students with disabilities through their involvement in social fraternities and sororities. The data were collected from seven undergraduate college students with disabilities who are members of fraternities and sororities and attend a large public research university in the mountain west region of the United States. The study revealed several findings that were organized under three superordinate themes: authentic peer relationships, barriers to belonging, and university environmental impacts. Throughout the study we are reminded of the need to address ableism and create inclusive and accessible spaces on college campuses for students with disabilities. Key implications include understanding the diversity of disability, revising policy and practice for co-curricular programming, and promoting disability inclusion.
Keywords: belonging; fraternity; sorority; disability; ableism; involvement